Design of damage tolerant and crack-free layered ceramics with textured microstructure. Issue 2 (February 2020) - Hofer, Anna-Katherina; Walton, Rebecca; Ševeček, Oldřich; Messing, Gary L.; Bermejo, Raul
Abstract: This work demonstrates damage tolerant behavior of ceramic laminates designed with residual stresses and free of surface edge cracks. Non-periodic architectures were designed by embedding 2 textured alumina (TA) layers between 3 equiaxed alumina-zirconia (AZ) layers. Compressive residual stresses of ∼ 250 MPa were induced in the textured layers. Indentation strength tests showed that textured compressive layers arrested the propagation of cracks. Results were compared to periodic architectures with the same volume ratio of TA and AZ materials. Crack propagation was arrested in both periodic and non-periodic designs; the minimum threshold-strength being higher in the latter. Non-periodic architectures with compressive layers as thin as ∼ 200 μm showed no evidence of surface edge cracks, yet still reached minimum threshold strength values of ∼ 300 MPa. In addition, the textured microstructure promoted crack bifurcation in the thin compressive layers and thus enhanced the damage tolerance of the material.